Highly Efficient and Durable Ammonia Electrolysis Cell Using Zirfon Separator - Haeyong Shin; Sang‐Mun Jung; Young Jin Lim; O‐Jung Yim; Byung‐Jo Lee; Kyu‐Su Kim; In‐Ho Baek; Jinwoo Baek; Jinhyeon Lee; Yong‐Tae Kim (Advanced Science)
Abstract Most studies on ammonia electrolysis have focused on anion exchange membranes (AEMs), which face limitations in operating conditions, such as pH and ammonia concentration. This study introduces a novel concept of an ammonia electrolysis cell (AEC) utilizing a Zirfon separator capable of operating under high pH and ammonia concentrations. The Zirfon‐based AECs achieve a peak current density of 915 mA cm−2, representing the highest reported value in AEC literature. Additionally, the Zirfon separator exhibits less conductivity degradation than AEMs during cycling tests (Zirfon 14.1%, AEMs 30.2%), demonstrating superior durability of the Zirfon‐based AEC.